KAJIAN LITERATUR SISTEMATIS TEORI PERTUKARAN SOSIAL DALAM HUBUNGAN DUA ARAH - Muttaqien, Priya Falaha (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
Social exchange theory (SET) is often perceived as a theory that only considers the profit-and-loss aspects of a two-way relationship. This theory is suspected of not considering other aspects, such as emotions and ethics, in viewing a relationship. Therefore, this study was conducted to prove the suspicion of social exchange theory. The study was conducted by collecting journal articles that have discussions related to social exchange theory, either as the main discussion or have issues related to the theory. Of the 44 journal articles reviewed, the results show that most of the research can be divided into 7 categories, namely educational institutions, tourism, marketing, management, psychology, public relations, culture. Management is the most category in the use of social exchange theory.. This finding corroborates that social exchange theory is stronger in the cost-benefit aspect in a two-way relationship. Keywords: Social exchange theory, dyad relationship, reward and cost, reciprocity